2017
DOI: 10.1107/s2052252517014324
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of XFEL serial diffraction data from individual crystalline fibrils

Abstract: Serial diffraction data collected at the Linac Coherent Light Source from crystalline amyloid fibrils delivered in a liquid jet show that the fibrils are well oriented in the jet. At low fibril concentrations, diffraction patterns are recorded from single fibrils; these patterns are weak and contain only a few reflections. Methods are developed for determining the orientation of patterns in reciprocal space and merging them in three dimensions. This allows the individual structure amplitudes to be calculated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…To this end, it was recently demonstrated that F-actin microfilaments, amyloid fibrils and pili flow align when injected within a microjet across a focused XFEL beam 31 , with the order of 100 polymers per sample being aligned to within 5°. Similar studies examined and sorted X-ray scattering from crystalline amyloid fibrils 32 and reported diffraction imaging of aligned amyloid fibrils held upon a graphene support 33 . These approaches therefore offer a promising path towards extending the resolution of single biomolecule imaging at an XFEL.…”
Section: Introductionmentioning
confidence: 97%
“…To this end, it was recently demonstrated that F-actin microfilaments, amyloid fibrils and pili flow align when injected within a microjet across a focused XFEL beam 31 , with the order of 100 polymers per sample being aligned to within 5°. Similar studies examined and sorted X-ray scattering from crystalline amyloid fibrils 32 and reported diffraction imaging of aligned amyloid fibrils held upon a graphene support 33 . These approaches therefore offer a promising path towards extending the resolution of single biomolecule imaging at an XFEL.…”
Section: Introductionmentioning
confidence: 97%
“…A disadvantage of using a highflow-rate injector with X-ray pulse rates of 120 Hz or less is high sample consumption, as large quantities of crystals pass unexposed between subsequent X-ray pulses and are thus wasted. Needle-shaped crystals can also suffer from preferred orientation along the injection-stream direction (Wojtas et al, 2017), which in many cases may hinder completeness. Furthermore, as these experiments are conducted rapidly, a sample in limited supply may be consumed before any problems with the setup (alignment, detector distance etc.)…”
Section: Liquid-jet Injectorsmentioning
confidence: 99%
“…If the crystal is stationary, the source is monochromatic and there is no beam divergence, what would the intensity be? This was a serious problem for Wojtas et al (2017) in their interpretation of XFEL (X-ray free-electron laser) data, requiring the partial capture of a reciprocal-lattice point and invoking angular tolerances to obtain some explanation of the data. If there were too many 'Bragg peaks' then they assumed that they were capturing data from more than one crystal and rejected the data.…”
Section: The Relationship Of the New Theory To The Ewald Spherementioning
confidence: 99%
“…This has led to a plethora of complex explanations to account for the data, e.g. Wojtas et al (2017).…”
Section: The Difficulties With 'Conventional Theory'mentioning
confidence: 99%